12. SOME EPIDEMIOLOGICAL AND HISTOPATHOLOGICAL CHARACTERISTICS OF LUNG CANCER IN HANOI IN 2015-2019 (Vietnam Journal of Community Medicine, 2023)
Objective: The study aimed to describe some epidemiological and histopathological characteristicsof lung cancer in Hanoi from 2015 to 2019. Methods: Retrospective study. Data were recorded from30 hospitals in Hanoi according to the principles of organization of population cancer registrationrecommended by the International Agency for Research on Cancer (IARC) from January 1, 2015 toDecember 31, 2019. The total number of disease stages (n=966) and histopathology (n=1351) wererecorded.Results: The disease was mainly detected at the late stage (71.2% were stage IV and 20.3% werestage III). The rate of stage IV lung cancer was highest in both urban and suburban areas. However,the urban area (74.9 %) was higher than the suburban area (69.0%). From stage 0 to III, the suburbswere higher than the urban area. According to histopathology results, adenocarcinoma had the highestrate (60.5%) and was higher in females than in males (79.4% vs. 53.7%). Small and squamous celllung cancer was more common among males (11.6% and 14.5%) than in females (1.1% and 5.4%).Conclusions: Lung cancer was found late, so the mortality rate was high. Therefore, it was necessaryto strengthen screening and early detection of lung cancer in people at risk to help choose appropriateinterventions to inhibit cellular activities and improve the patient’s quality of life.
Keywords: Histopathology, epidemiology, lung cancer, Hanoi.